2019
DOI: 10.1029/2019jd030836
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Intertropical Discontinuity Region and the Heat Low in Dust Emission and Transport Over the Thar Desert, India: A Premonsoon Case Study

Abstract: Key Points Satellite observations and Meso‐NH model simulations are used to investigate an intense dust storm over north India in June 2018 Dust is mostly confined below 2 km in the monsoon flow over the Thar desert, northwest India and at ~3 km along the Ganges Valley The dust was accumulated in an arc‐shaped cloud in the convergence zone between the southwesterlies and the northwesterlies: the ITD

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 112 publications
5
25
0
Order By: Relevance
“…It is to be noted here that the enhanced aerosol loading over the IGB is usually the main cause of increase loading over the BoB through IGB-outflow ( Srinivas et al, 2011 ; Tiwari et al, 2016 ; Singh et al, 2020 ). Furthermore, the IGB is situated in the vicinity of the Desert regions, and thus largely impacted by the frequent occurrence of dust aerosols during March-June ( Pandithurai et al, 2008 ; Srivastava et al, 2014 ; Dumka et al, 2019 ) even though negative change in aerosol loading indicate that anthropogenic aerosol emission override the natural local or transported aerosols. The Sentinel - 5 P satellite observations also illustrated the improved air quality of Indian subcontinent during COVID-19 lockdown time period ( Shehzad et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…It is to be noted here that the enhanced aerosol loading over the IGB is usually the main cause of increase loading over the BoB through IGB-outflow ( Srinivas et al, 2011 ; Tiwari et al, 2016 ; Singh et al, 2020 ). Furthermore, the IGB is situated in the vicinity of the Desert regions, and thus largely impacted by the frequent occurrence of dust aerosols during March-June ( Pandithurai et al, 2008 ; Srivastava et al, 2014 ; Dumka et al, 2019 ) even though negative change in aerosol loading indicate that anthropogenic aerosol emission override the natural local or transported aerosols. The Sentinel - 5 P satellite observations also illustrated the improved air quality of Indian subcontinent during COVID-19 lockdown time period ( Shehzad et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Multiple reports suggested that an increase in the nonaccidental mortality by up to more than 10% due to prolonged (≥3 days) high PM10 episodes (Kim et al, 2018a(Kim et al, , 2018bPizzo & Clerico, 2012;Wang et al, 2018;Wong et al, 2017;Zhang et al, 2017;Zhou et al, 2015), much higher than the mortality rate caused by shorter duration events (<3 days). (ii) Severe widespread prolonged dust events are triggered and maintained by persistent synoptic circulations (e.g., Beegum et al, 2018;Dumka et al, 2019;Hamidi et al, 2017Hamidi et al, , 2014Houssos et al, 2015;Knippertz & Fink, 2006;Knippertz & Stuut, 2014;Shao et al, 2010;Solomos et al, 2017). A synoptic circulation should sustain at least 3 days to reach its persistent nature (e.g., Guemas et al, 2010Guemas et al, , 2009Kyselý & Domonkos, 2006;Miller et al, 2020).…”
Section: Identification Of Extreme Dust Eventsmentioning
confidence: 99%
“…Thermal heat lows and convergence zones between moist and dry air masses are ubiquitous features of tropical and subtropical regions (i.e. Flamant et al, 2007;Dumka et al, 2019). They play a crucial role in modulating the mesoscale meteorological features in these regions, such as the mesoscale convection, dust storms and monsoon surge and associated rain (e.g.…”
Section: Introductionmentioning
confidence: 99%